Making Fitness to Plead Fit for Purpose - Shah, Amar (International Journal of Criminology and Sociology, 2012)
In the England and Wales criminal justice system, consideration of a defendant’s ability to stand trial is known as ‘fitness to plead’. No accused person may face trial unless they are fit to plead to the charges against them. The fitness to plead criteria date back to the 19th century, and have been virtually unchanged. Developed from case law relating to sensory impairment and intellectual disability, they are now routinely utilised for severe and enduring mental illnesses, predominantly psychotic disorders. The fitness to plead criteria are no longer appropriate to meet modern understanding of complex mental disorders, and are shamefully archaic in comparison to civil capacity legislation. This paper outlines the development of the fitness to plead criteria and process, summarises current criticisms and proposes potential reform in this fundamental area of mental health law.